2003
DOI: 10.1051/0004-6361:20030703
|View full text |Cite
|
Sign up to set email alerts
|

Deep optical observations of the fields of two nearby millisecond pulsars with the VLT

Abstract: Abstract. We report on deep VLT observations of the fields of two nearby, isolated millisecond pulsars, PSR J1744-1134 and PSR J1024-0719. Both objects are old neutron stars with characteristic age τ ≥ 10 9 yr and have relatively high spin-down flux. They have been detected earlier as X-ray sources by ROSAT HRI observations and were considered good candidates for non-thermal emission in the optical bands. Our observations set an upper limit of B = 26.9, V = 26.3 and R = 26.0 for PSR J1744-1134. In the case of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 37 publications
2
20
0
Order By: Relevance
“…The pulsar is undetected down to a flux limit of V ∼ 27.8, the deepest obtained so far for an object of this class. Unfortunately, this result adds to the list of non-detections of millisecond pulsars deriving from (shallower) observations recently performed with the VLT, namely PSR J1024−0719, PSR J1744−1134 (Sutaria et al 2002) and PSR J0030+0451 (Koptsevich et al 2002). Future observations of these objects in the near-UV with the HST will probably offer higher chanches of detection.…”
Section: Discussionmentioning
confidence: 74%
“…The pulsar is undetected down to a flux limit of V ∼ 27.8, the deepest obtained so far for an object of this class. Unfortunately, this result adds to the list of non-detections of millisecond pulsars deriving from (shallower) observations recently performed with the VLT, namely PSR J1024−0719, PSR J1744−1134 (Sutaria et al 2002) and PSR J0030+0451 (Koptsevich et al 2002). Future observations of these objects in the near-UV with the HST will probably offer higher chanches of detection.…”
Section: Discussionmentioning
confidence: 74%
“…All were identified prior to the launch of Fermi, mostly in the 1990s (Mignani 2011). In the last decade possible counterparts were found for PSR B1951+32 (Butler et al 2002) and the solitary MSP PSR J1024−0719 (Sutaria et al 2003), prior to their detection as gamma-ray pulsars. Furthermore, PSR J1124−5916 has been associated with a bright, optical PWN, although no point source has been identified as a potential counterpart (Zharikov et al Notes.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Nonetheless, deep VLT observations of the field of PSR J1024−0719 conducted by Sutaria et al (2003) revealed the presence of two stars near the position of the pulsar. One possibility could therefore be that PSR J1024−0719 is associated with one of the two nearby stars, in a wide orbit causing the MSP to undergo acceleration along our line of sight.…”
Section: Psr J1024−0719mentioning
confidence: 99%